The Moderating Role of External Auditor on the Relationship Between Corporate Governance and Earnings Management: Evidence from Amman Stock Exchange in Jordan - Fawwaz Ali Taha Ababneh (Universiti Sains Islam Malaysia, 2024)
Matric: 4160298 (FEM)